Peanut (Arachis hypogaea) consumption improves glutathione and HDL-cholesterol levels in experimental diabetes - YARAT, AYŞEN; ALTURFAN, EBRU IŞIK (WILEY, 2008)
The aim of this investigation was to assess the influence of peanut (Arachis hypogaea) consumption on oxidant-antioxidant status and lipid profile in Streptozotocin (STZ) induced diabetic rats. 32 rats were divided into 4 groups as control, control+peanut, diabetic, diabetic+peanut. Control and diabetic groups were fed on standard rat chow whereas control+peanut and diabetic+peanut were fed on standard rat chow supplemented with 0.63 g % peanut for 12 weeks. Serum glucose levels, lipids, Glutathione (GSH), lipid peroxidation (LPO) and atherogenic index (AI) levels were determined at the end of the experiment. In the diabetic group TG (Triglyceride), TC (Total cholesterol), LDL-C (LDL-cholesterol) levels and atherogenic indexes increased significantly whereas HDL-C (HDL-cholesterol) level decreased significantly compared to the control group. The supplementation with peanut in the diabetic group led to significantly higher HDL-C levels and lower AI levels compared to diabetic group. Peanut consumption increased GSH levels significantly both in control and diabetic groups. In conclusion, this study shows that peanut consumption may improve oxidant-antioxidant status in healthy and diabetic status without increasing blood lipids. Moreover, increased HDL-C levels and decreased AI levels in diabetic rats indicate that, peanut consumption may have protective effects against cardiovascular complications of diabetes. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: peanut; diabetes; oxidant-antioxidant status; serum lipids; PARSLEY PETROSELINUM-CRISPUM; INSULIN SENSITIVITY; FATTY-ACIDS; DIETARY; DISEASE; PLASMA; RISK; HYPERGLYCEMIA; GLYCATION; WOMEN